Exploring the potential of SWOT mission for reservoir monitoring in Mahanadi basin. Issue 3 (1st February 2022) - Nair, Akhilesh S.; Verma, Kaushlendra; Karmakar, Subhankar; Ghosh, Subimal; Indu, J.
Abstract: The Surface Water and Ocean Topography (SWOT) mission, which is scheduled to launch in 2022, would offer India with unprecedented hydrologic applications. This study presents the preliminary results of the CNES Large-Scale SWOT Hydrology Simulator to illustrate how SWOT data can be used to monitor reservoir water levels. Except for some factors such as effects due to topography, and error due to idealized water detection, the CNES simulator accounts for practically all of the probable noise expected in future SWOT data. In this paper, we look at how SWOT can be used to monitor reservoirs in difficult situations. SWOT will monitor the reservoir in two swaths in this case, with an unmonitored zone in the middle. This paper provides a strategy for extrapolating data across two swaths to determine reservoir volume. The results demonstrate that the proxy water surface elevation (WSE) created by the CNES simulator has a great potential in scientific research relating to reservoir characteristics and surface water dynamics. It is observed that the reservoir volume estimated using proxy SWOT data has a maximum bias of −7.65 % and a minimum bias of −2.19 %.